Screening the Dark Side of Love - Ritzenhoff, Karen A. author. aut Link
XXIV, 256 p. 18 illus.
Keywords: How can love be understood globally as a problematic transgression rather than the narrative of "happy endings" that Hollywood has offered? The contributors utilize varying methodologies of textual analysis, psychoanalytic models, and cultural critique and engage with a broad range of films to explore issues of gender identity and spectatorship.